Исследование сгонно-нагонных колебаний уровня Азовского моря с использованием прогностических полей ветра - Фомин, В.В.; Шульга, Т.Я. (Видавничий дім "Академперіодика" НАН України, 2007)
With the use of the forecast fields of winds and atmospheric pressure, changes in the sea level are studied by the method of mathematical modeling. The results of numerical calculations are compared with the data of direct measurements of the sea level on coastal stations. The degree of sensitivity of the rated values of ebbs and floods to the surface friction coefficient is studied.